Formulating Criminal Liabilities Regarding Online Prostitution - Laksana, Trio Angga; Ohoiwutun, Y.A. Triana; Tanuwijaya, Fanny (University of Jember, 2019)
This study aims to obtain similarities and differences regarding legal formulation in online prostitution. Hitherto, prostitution has remained to exist in Indonesian society. In context, the existing perpetrators of prostitution do not peddle conventionally but also virtually, in which online prostitution that gradually increases is a common term that refers to this phenomenon. The current law enforcement against perpetrators of online prostitution performs as the consequence of the national law in which national laws have yet remained to accommodate in criminalizing perpetrators of online prostitution. The criminalization of perpetrators in online prostitution may contrast with the principle of legality so that national laws should accommodate perpetrators of online prostitution regarding their criminal liability. In particular, these national laws should address whether to prohibit the attitude that proliferates online prostitution so that perpetrators of online prostitution should be accountable for their crimes. Henceforth, this measure intends to avoid the overlap of the principle of legality in criminal law. Keywords: Online Prostitution, Criminal Liabilities, Principle of Legality.